1986
DOI: 10.1111/j.1365-2559.1986.tb02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymph‐node infarction and malignant lymphoma: a multicentre survey of European, English and American cases

Abstract: A multicentre study of 51 cases of lymph-node infarction seen in the 30-year period 1956 to 1985 was conducted in order to assess both the short- and long-term prognostic implications of the condition. In 14 cases malignant lymphoma was found synchronously with the infarct. Of the remaining 37 patients with apparently 'benign' lymph-node infarction only six showed manifestations of malignant lymphoma in the follow-up time studied (mean = 48 months; range 1-156 months). These subsequent malignant lymphomas all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…A previous study reported one lymph node infarction in every 13,000 surgical biopsies. 5 Over a period of approximately 10 years, only 51 cases of lymph node infarction were encountered in six different histopathology departments in Switzerland, the …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported one lymph node infarction in every 13,000 surgical biopsies. 5 Over a period of approximately 10 years, only 51 cases of lymph node infarction were encountered in six different histopathology departments in Switzerland, the …”
Section: Discussionmentioning
confidence: 99%
“…5,6,7,8 In previous reports, lymph node infarction accompanied by Hodgkin lymphoma was rare. 5,6,9 Even in infarcted lymph nodes, L26 (anti-CD20 antibody) has been found to be of diagnostic value, 7,8,10 especially for diagnosis of B-cell lymphoma. In our case, L26 staining was negative in both the infarcted sample and in the sample that was used to diagnose Hodgkin lymphoma.…”
Section: Xxxxx Xxxxx Xxxxxmentioning
confidence: 98%
“…14 Neoplastic lesions most commonly associated with infarction are malignant lymphoma and metastatic malignancy. 15 Massive infarction of the lymph node should raise the suspicion of lymphoma and must be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,8 However, malignant lymphoma with extensive necrosis is extremely difficult to diagnose on the basis of morphology. Although necrotic tissue is, in general, thought to be unsuitable for immunohistochemical analysis because of the loss of antigenicity and nonspecific staining, it is sometimes useful in elucidating the underlying processes in lymph node infarction.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Among malignant lymphoproliferative disorders, lymph node infarction appears to be most frequently seen in diffuse large B-cell lymphoma (DLBCL), followed by follicular lymphoma (FL), [4][5][6] with other types being rare. To our knowledge, only a single case of classical Hodgkin's lymphoma (cHL) has been reported as one of 10 cases of malignant lymphoma associated with lymph node infarction in the English literature, but the report focused on antigen preservation.…”
Section: Introductionmentioning
confidence: 99%